Immunity as a predictor of anti-malarial treatment failure: a systematic review - Katherine O’Flaherty (Malaria Journal, 2017)
Abstract Background Naturally acquired immunity can reduce parasitaemia and potentially influence anti-malarial treatment outcomes; however, evidence for this in the current literature provides conflicted results. The available evidence was synthesized to determine and quantify the association between host immunity and anti-malarial treatment failure. Methods Four databases were searched to identify studies investigating malaria antibody levels in patients receiving anti-malarial treatment for symptomatic malaria with treatment failure recorded according to the World Health Organization classification. Odds ratios or hazard ratios were extracted or calculated to quantify the association between malarial antibody levels and treatment failure, and findings from different studies were visualized using forest plots. Results Eight studies, including patients with falciparum malaria treated with mono- and combination therapy of artemisinin derivatives, sulfadoxine, pyrimethamine and chloroquine, were identified. Reported and calculated effect estimates varied greatly between studies, even those assessing the same antigens and treatments. An association between blood-stage IgG responses and treatment efficacy was observed. The greatest magnitudes of effect were observed for artemisinin [OR/HR (95% CI) range 0.02 (0.00, 0.45)–1.08 (0.57, 2.06)] and chloroquine [0.24 (0.04, 1.37)–0.32 (0.05, 1.96)] treatments, and larger magnitudes of effect were observed for variant surface antigen responses [0.02 (0.00, 0.45)–1.92 (0.94, 3.91)] when compared with merozoite specific responses [0.24 (0.04, 1.37)–2.83 (1.13, 7.09)]. Conclusions Naturally acquired malarial immunity is associated with reduced anti-malarial treatment failure in malaria endemic populations. Anti-malarial IgG effects treatment outcome differently for different anti-malarial drugs and antigen targets, and had the greatest impact during treatment with the current first-line treatments, the artemisinins. This has implications for the assessment of the therapeutic efficacy of anti-malarials, particularly in the context of emerging artemisinin resistance.